Evaluating English Textbooks: A Cultural Matter - Ximena Bonilla Medina (Asociación Colombiana de Profesores de Ingles, 2008)
Globalization has brought about many changes in the concept of culture. One of those changes has been directly reflected in the way language is seen in the contexts of foreign language teaching. This article explores how culture has been represented in an English textbook and the way this conception may build students' perceptions about English speaking countries. The argumentation of this study is supported by the analysis of some excerpts taken from a recognized English textbook currently used in several institutions in Bogotá, a survey that shows some teachers' opinions about textbooks and the book under discussion, and the way they evidence culture in them. This reflection searches for a general understanding of the ways teachers can critically evaluate culture in textbooks, therefore, discovering stereotyped visions of culture.